Spirit possession in a contemporary British religious network: a critique of New Age movement studies through the sociology of power - Wood, Matthew R. (1999)
Studies of phenomena classed as part of the New Age Movement have become increasingly common in recent years. This Thesis develops a new perspective on these through the use of anthropological and sociological analysis of structures of social power and the contextualisation of symbols and discourse. Research was based on a two and a half year ethnographic study of a network in Nottinghamshire, Britain, which included a meditation group and a spiritual fair. Spirit possession was seen as particularly important to these, in the forms of channelling and mediumship. The concept of nonformative spirituality was used to delineate the network as lacking enduring leadership and authority, such that participants' experiences varied within groups and practices. Thus, the network was not seen as part of a movement, but as a collection of informal groups linked through people's practices. Theory of bodily performance, with a critical analysis of the sociology of knowledge, was used to interpret the four sorts of practices in the network: channelling, meditation, holistic health therapies and divination. By paying attention to people's spiritual biographies, their careers of seekership were understood to develop through dissonant experiences. Nonformative spirituality was compared with those more formative groups which it drew upon, such as spiritualism, the Anthroposophical Society and occult study groups, thus providing a broader picture of its place in contemporary Britain.